Pemanfaatan Sumber Daya Alam Pesisir Secara Berkelanjutan Melalui Pengolahan Makro Alga sebagai Oleh-Oleh Khas Pantai Krakal - Nurmiyati, Nurmiyati (Prosiding KPSDA, 2015)
Exploration and utilization of seashore potency has to be done sustainably. One of the most valuable plants at Krakal Beach, Gunung Kidul is macroalgae which has not been identified and produced well. Krakal Beach is one of the beach tourism area, which has not been developed yet. To increase the income of owners of the shops in this tourism area, a community development had been held from June to October 2013. The target of this activity were women, which work as shop owner, and join the group of shop owner called Kelompok Pedagang Sido Mulyo Pantai Krakal. The participants had been trained four times, i.e. to understand the sea potency and sustainable development; how to make a jam and sweets made from Euchema sp., and also make crispy chips made from Ulva lactuca, one of the commonly found algae at Krakal Beach. Other topics of training were product packaging; and marketing and promoting the product. The result of this community development was increasing of awareness of the participant to explore and utilize the local potency sustainability, and as well as the increasing of their income from unique-local macro algae product.